건식 공정에서 자발적 환원 반응에 의한 AEM 수전해용 Fe-Ni 나노 촉매 제조 및 특성 - 이재영(JAEYOUNG LEE); 이홍기(HONGKI LEE) (한국수소 및 신에너지학회 논문집, 2024)
Fe-Ni nanocatalysts loaded on carbon black were prepared via spontaneous reduction reaction of iron (II) acetylacetonate and nickel (II) acetylacetonate in dry process. Their morphology and elemental analysis were characterized by scanning electron microscopy, transmission electron microscopy (TEM), and energy dispersive X-ray analyzer. The loading weight of the nanocatalysts was measured by thermogravimetric analyze and the surface area was measured by BET analysis. TEM observation showed that Fe and Ni nanoparticles was well dispersed on the carbon black and their average particle size was 4.82 nm. The loading weight of Fe-Ni nanocatalysts on the carbon black was 6.83-7.32 wt%, and the value increased with increasing iron (II) acetylacetonate content. As the Fe-Ni loading weight increased, the specific surface area decreased significantly by more than 50%, because Fe-Ni nanoparticles block the micropores of carbon black. I-V characteristics showed that water electrolysis performance increased with increasing Ni nanocatalyst content.